Matematična anksioznost - Lutovac, Sonja (Revija za elementarno izobraževanje, 2008)
Mathematics Anxiety. Mathematics anxiety is commonly defined as a feeling of tension, apprehension or fear that interferes with a students’ performance in math classes. Although the causes of math anxiety are undetermined, some teaching styles have been identified as risk factors. Mathematics anxiety can cause personal and educational problems. This can lead to the common tendency of avoiding mathematics, which may ultimately hinder math competence and make important career paths unobtainable. It is imperative that teachers understand the causes of their students’math anxiety and offer them proper help. This article defines the current problem and provides a review of selected literature on the causes and consequences of mathematics anxiety and assessment and intervention programs. Some findings about math anxiety and gender and age differences are given.Mathematics anxiety is also a common phenomenon among elementary school teachers and can seriously interfere with their teaching. For this reason, the article also presents a viewpoint of this particular problem.